Pengaruh Etos Kerja terhadap Kinerja Karyawan Perusahaan di Indonesia - Didit Darmawan; Muhammad Afian Firmansyah; Rahayu Mardikaningsih (Lembaga Pengembangan Kinerja Dosen, 2026)
In today’s era of multisectoral competition, the excellence of human resources (HR) is a crucial determinant of a company’s sustainability, as the achievement of its vision and mission heavily depends on employees who possess a resilient mindset and work ethic. This study was conducted to comprehensively examine the impact of work ethic on employee performance, drawing on various previous research findings. The research method applied was a literature review using a qualitative descriptive approach, synthesizing ten relevant scientific studies. The results of the data analysis consistently showed that work ethic has a positive and significant effect on employee performance. The findings confirm that work ethic is not merely a physical activity, but rather a manifestation of personality that motivates employees to perform at their best. From a managerial perspective, this study recommends that companies prioritize programs aimed at instilling professional values and fostering character development, as these strategies are crucial for creating a productive work culture, enhancing operational effectiveness, and strengthening the organization’s competitiveness in the face of global business challenges.